Introduction to banking - Olalusi, Foluso (Ibadan Evans Brothers)
The book places emphasis on the practical aspects of banking, briefly analysed, and yet provides an insight into the final stage of the Banking Diploma of the Institute of Bankers, Associate of Chartered Institute of Secretaries, and allied professional bodies.
Includes index
osc 10/4/17
Loans
Keywords: Banks and banking; Banking - Nigeria